Hubungan kepercayaan diri dengan gangguan makan anorexia nervosa pada remaja di SMAN 4 Kota Langsa - Sri Ayu Melani; Hasanuddin Hasanuddin; Nina Siti Salmaniah Siregar (Politeknik Kesehatan Kemenkes Aceh, 2021)
Background: One of the effects of the transition period is the perception that young women look beautiful by over-dieting so that it can cause eating disorders that affect themselves and their social relationshipsObjectives: This study aims to see the relationship between self-confidence and eating disorder anorexia nervosa in adolescentsMethods: This study uses correlational quantitative methods by analyzing the dynamics between phenomena, both risk factors, and effect factors. The design was cross-sectional to see the relationship between exposure status (risk factors) and observed effectsResults: The analysis showed that self-confidence had a significant relationship with eating disorder anorexia nervosa in adolescents, amounting to 28.42%, also supported by the coefficient value of the property (rx1y= -0.865) with a significance level (p= 0.000 < 0.01) significantConclusion: In conclusion, the hypothesis is accepted, because rx1y has a negative value, eating disorder Anorexia Nerves has a very significant negative relationship with self-confidence.